FREQUENCY AND RISK FACTORS OF COMPLICATIONS OF SURGICAL TREATMENT OF CORNEAL DISEASES - Maharramov, P.M. (World of Medicine and Biology, 2021)
112 patients (80 men, 32 women; 89 and 39 eyes, respectively) aged from 20 to 48 years with various corneal pathologies were retrospectively examined. The patients were operated using the following types of operations: intrastromal implantation of the corneal segment; crosslinking of corneal collagen using ultraviolet radiation and riboflavin; combined use of these methods in various variants with and without photorefractive and phototherapeutic keratectomy. Intraoperative complications were observed mainly during implantation of the intrastromal segments of the cornea. 10 % of various types of intraoperative complications accounted for 100 such operations. The combined use of corneal collagen crosslinking with both photorefractive keratectomy and phototherapy keratectomy is associated with the same risk of postoperative complications. The risk of postoperative complications is relatively high in patients aged 30 years and older, with a preoperative level of visual acuity without correction of less than 0.2 and with a central corneal thickness of 470 microns.